Partner support and relationship quality as potential resources for childbirth and the transition to parenthood - Lisa Hoffmann; Norbert Hilger; Elena Riolino; Annika Lenz; Rainer Banse (BMC, 2023)
Abstract Background The aim of the present paper was to explore the role of partners for the stressful life events of birth and the transition to parenthood. Methods In a first prospective longitudinal study (N = 304 dyads) we tested whether relationship quality positively predicted fewer interventions during labor and birth, a more positive birth experience, and better well-being during the first six weeks after birth. In a second study we surveyed mothers (N = 980; retrospective quasi-experimental design) who had given birth during the first lockdown of the COVID-19 pandemic in spring 2020 - some in the absence of their partners - to test the assumption that regardless of relationship quality, the presence of the partner was positively related to low-intervention births and the birth experience. Results The results of the longitudinal study (Study 1) could be integrated into a Single Indicator model. They revealed that a high relationship quality assessed between week 5 and week 25 of pregnancy had a positive effect on birth experience for the mother and on psychological well-being during the transition to parenthood for both mothers and fathers. Results of the retrospective quasi-experimental field study (Study 2) revealed that the continuous presence of the partner was associated with a higher probability of a low-intervention birth and a more positive birth experience. Presence of a partner for only part of the birth did not positively predict labor and birth, but did positively predict the birth experience. The effects were independent of relationship quality. Conclusion The results of both studies highlight the importance of partners for psychological well-being during labor and birth and the transition to parenthood.